Biomechanical and morphological study of a new elastic mesh (Ciberlastic) to repair abdominal wall defects. (June 2016) - Calvo, B.; Pascual, G.; Peña, E.; Pérez-Khöler, B.; Rodríguez, M.; Bellón, J.M.
Abstract: The aim of this study was to conduct a preclinical evaluation of the behaviour of a new type of abdominal LW prosthesis (Ciberlastic), which was designed with a non-absorbable elastic polyurethane monofilament (Assuplus, Assut Europe, Italy) to allow greater adaptability to mechanical area requirements and higher bio-mimicking with the newly formed surrounding tissues. Our hypothesis was that an increase in the elasticity of the mesh filament could improve the benefits of LW prostheses. To verify our hypothesis, we compared the short- and long-term behaviour of Ciberlastic and Optilene ® elastic commercial meshes by repairing the partially herniated abdomen in New Zealand White rabbits. The implanted meshes were mechanically and histologically assessed at 14 and 180 days post-implant. We mechanically characterized the partially herniated repaired muscle tissue and also determined mesh shrinkage at different post-implant times. This was followed by a histological study in which the tissue incorporation process was analysed over time. The new prosthesis designed by our group achieved good behaviour that was similar to that of Optilene ®, one of the most popular LW prostheses on the market, with the added advantage of its elastic property. The mechanical properties are significantly lower than those of the polypropylene Optilene ® mesh, and the new elastic mesh meets the basic mechanical requirements for positioning in the abdominal wall, which was also demonstrated by the absence of recurrences after implantation in the experimental model. We found that the growth of a connective tissue rich in collagen over the hernial defect and the proper deposit of the collagen fibres in the regenerated tissue substantially modified the original properties of the mesh, thereby increasing its biomechanical strength and making the whole tissue/mesh stiffer.